2021
DOI: 10.1002/iub.2526
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Socs3 knockdown attenuates postnatal obesity caused by an early life environment of maternal obesity and intrauterine overnutrition in progeny mice

Abstract: Pathological states in the early life environment of mammalian offspring, including maternal obesity and intrauterine overnutrition, can induce obesity and metabolic disorder later in life. Leptin resistance caused by upregulation of Socs3 in the hypothalamus of offspring was believed to be the main mechanism of this effect. In this study, obese mother (OM) and lean mother (LM) models were generated by feeding C57BL/6N female mice a high‐fat diet or standard lean diet, respectively. Additionally, an obese moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…74 Zhu et al provided evidence showing that maternal Socs3 knockdown attenuates the obesity phenotype and metabolic disorder in offspring. 75 Our results showed that the MHFD offspring exhibited high serum leptin levels. However, hypermethylation and lower expression of the hypothalamic Lepr gene were observed in the offspring from the MHFD dams compared with the offspring from the control dams.…”
Section: Papermentioning
confidence: 55%
See 1 more Smart Citation
“…74 Zhu et al provided evidence showing that maternal Socs3 knockdown attenuates the obesity phenotype and metabolic disorder in offspring. 75 Our results showed that the MHFD offspring exhibited high serum leptin levels. However, hypermethylation and lower expression of the hypothalamic Lepr gene were observed in the offspring from the MHFD dams compared with the offspring from the control dams.…”
Section: Papermentioning
confidence: 55%
“…74 Zhu et al provided evidence showing that maternal Socs3 knockdown attenuates the obesity phenotype and metabolic disorder in offspring. 75…”
Section: Discussionmentioning
confidence: 99%
“…AKTIP‐A mouse mutants show developmental abnormalities (Anselme et al., 2007 ). HSPB6 is involved in the regulation of angiogenesis (Vafiadaki et al., 2020 ), SCNN1G plays a role in water homeostasis (Hobbs et al., 2013 ), while SOCS3 is involved in the regulation of food intake (Zhu et al., 2021 ). DNA methylation patterns of 5′‐flanking regions have been shown to correlate with gene expression, at least for SCNN1G (Pierandrei et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These DMRs were found within the gene bodies of HSPB6 , PGS1 , SCNN1G , SOCS3 , as well as two uncharacterised genes. HSPB6 is involved in the regulation of angiogenesis (Vafiadaki, Arvanitis, Eliopoulos, Kranias, & Sanoudou, 2020), SCNN1G plays a role in water homeostasis (Hobbs et al, 2013), while SOCS3 is involved in the regulation of food intake (Zhu et al, 2021). DNA methylation patterns of 5’-flanking regions have been shown to correlate with gene expression, at least for SCNN1G (Pierandrei et al, 2021).…”
Section: Discussionmentioning
confidence: 99%